MORPHOLOGY VARIATION OF METARHIZIUM ANISOPLIAE FROM SOIL IN NORTH SUMATRA AREAS - Sirait, Desianty Dona Normalisa; Tobing, Maryani Cyccu; Safni, Irda (Universitas Negeri Medan, 2017)
AbstractMetarhizium anisopliae is an important entomopathogenic fungus that mainly used for biological control. Isolates of M. anisopliae extracted from soil from 15 oil palm plantations located in several districts on the Province of North Sumatra, Indonesia have been investigated to identify their morphological diversity. The morphology of assessed fungi was constructed in the the form of conidia, conidia size, color and shape colony and growth diameter of the 15 isolates. All of conidia forms showed cylindrical shape and string together. The length/width (Î¼m) ratio of conidia size was minimum 2,16 and maximum 3,54. The highest growth rate isolates were found in M3 (Bandar Selamat) and M12 (Mancang) treatment and the lowest rate was M11 (Teluk Parit Kaca) treatment. The color of colonies were varied among the isolates. They were greenish yellow, dark green, yellowish and showing zonation/no zonation.Keywords : Metarhizium anisopliae, biological character, morphological diversity